Calidad de servicio y satisfacción del cliente de la cooperativa de ahorro y crédito Sierra Centro matriz Latacunga - Rodríguez Chicaiza, Allison Cristina (2022)
This research work focused on identifying the relationship between service quality and customer satisfaction within the Sierra Centro Matriz Latacunga Savings and Credit Cooperative, considering the variables of service quality and satisfaction as dimensions. The methodology used for this research corresponded to a quantitative study, where a finite population was taken, applying a sample of 357 members, for which the survey technique was used to obtain the information through a structured questionnaire. Service quality is essential for financial companies, since they allow customer loyalty and, in turn, generate customer satisfaction regarding their needs and expectations. For this reason, this variable plays an essential role in any organization, since over time institutions must reinvent themselves and adapt to the new demands, needs and desires of customers. The problem indicates that the Sierra Centro Matriz Latacunga Savings and Credit Cooperative does not have an evaluation through the SERVQUAL and CSAT model, consequently, the institution's staff does not give due importance to the development of customer service. In addition, it does not have a correct control and evaluation regarding customer satisfaction. For this reason, if new internal improvement actions are not adopted, customers will prefer other financial institutions. For these reasons, within the research work, the SERVQUAL and CSAT model was determined, to study the four dimensions: quality, service, satisfaction, customer. Which allowed to establish if in the company the clients are satisfied with the services offered. Likewise, the research proposal is presented, which proposes the creation and application of strategies aimed at the financial institution, which are based on customer service and satisfaction, for which the most important indicators such as digitalization, personalized assistance. In conclusion, customer service is considered a very important factor today within financial institutions, since at the time of its creation they are governed by a quality code, it is of vital importance for the entire company to comply with the indicated quality standards, which will facilitate achieving the proposed objectives